Works by Maria Shimanovskaya in The Reflection of Slavic Style Line of Biedermeier - Chuprina, Nataliia (Journal of History Culture and Art Research, 2019)
The aim of the work is the analysis of features of Biedermeier in the legacy of M. Shimanovskaya based on the detailed investigation of Mazurkas and Nocturnes which reflect the main characteristics of the “high Biedermeier”, distinguished by religious and spiritual traits. The methodological base of the given research is the intonation system of the comparative school of B. Asafiev, representation of the results of contribution of authors which were aimed at the development of problems of Slavic Biedermeier by the means of various types of studies. Scientific novelty lies in the predominant accentuation of the Biedermeier style line in the heritage of M. Shimanovskaya. On the whole, M. Shimanovskaya does not cross the limits of abilities of “easy piano”, giving preference to expression achievement through the eclectic stylistic combinations, while demonstrating an emphasized miniaturization of national or the expansion of culturally dominant quality of the genre. The mentioned eclecticism does not tough upon the demonic opposition of romanticism in any perceptible way, apart from the “review” of the latter in the structure of Nocturne. This is the key point of the Biedermeier logic of the “great in small”, which also emphasizes the romantic principles in the expressiveness of M. Shimanovskaya`s works and performing art.